Proposal for Evaluating the Efficiency of Production Processes Using External and Internal Key Performance Indicators - Sujova, Erika; Vyslouzilova, Daniela; Babic, Ivan (Manufacturing Technology Journal, 2024)
The paper focuses on proposing a method for implementing key performance indicators (KPIs) to assess the effectiveness of manufacturing processes. For the evaluated processes of precision parts machining, the share of non-conforming products was proposed as a KPI, evaluated as both an exter-nal and an internal indicator. The external indicator EXTppm expressed the quantity of faulty prod-ucts to the volume of production. Its monthly development during 2022 was evaluated. The internal KPI represented the internal share of non-conforming products INTppm during 2022 which was re-lated to the order of part A. Towards the conclusion causes for not attaining the targeted KPI values are pinpointed, and recommendations are put forth to enhance the productivity of manufacturing processes.
Keywords: Key Performance Indicator (KPI); Process Performance; Faulty Product; Non-conforming Product; Maintenance